Meningkatkan Kreativitas melalui Kegiatan Membatik Ecoprint Anak Usia 5-6 Tahun - Arika; Siti Munawarah (Universitas Lancang Kuning, 2023)
In increasing children's creativity, activities are needed to that children can express their creativity. One activity to increase children's creativity is making ecoprint batik. The purpose of this study was to determine the development of creativity, to find out the application of ecoprint batik activities and to find out the increase in creativity through ecoprint batik activities in children aged 5-6 years at Aisyiyah Bustanul Athfal Kindergarten, Pasiran Village, Bantan District. This type of research is Classroom Action Research, which is carried out in two cycles. Data collection techniques used are observation and documentation. The results of this study are: Increasing children's creativity in Aisyiyah Bustanul Athfal Kindergarten in Pasiran Village by implementing ecoprint batik activities, the results of an analysis of the level of creativity of children in cycle I obtained a percentage of 53.4% ​​in the Beginning to Develop category, while in cycle II, children's creativity increased to 71.7% with the criteria Developing According to Expectations (BSH). It was concluded at the end of the cycle, that ecoprint activities can increase children's creativity.